2015
DOI: 10.3989/loquens.2015.023
|View full text |Cite
|
Sign up to set email alerts
|

Predicting segmental substitution errors in aphasic patients with phonological and phonetic encoding impairments

Abstract: Citation / Cómo citar este artículo: Anna Marczyk and Lorraine Baqué. Predicting segmental substitution errors in aphasic patients with phonological and phonetic encoding impairments. Loquens, 2(2), e023. doi: http://dx.doi. org/10. 3989/loquens.2015.023 ABSTRACT: This paper analyses the factors that predict substitution errors produced by four Broca's and four conduction aphasic subjects, all native speakers of Spanish, in reading and repetition tasks. Errors were elicited using a list of words where type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 55 publications
0
3
0
5
Order By: Relevance
“…Actually such a 'uniform' co-variation between two cues has also been associated in studies about the phonetic realisation of segmental phonological oppositions with 'clear speech' (concomitant strengthening) (Uchanski, 2005;Ferguson & Kewley-Port, 2007) and reduction processes (concomitant weakening) phenomena (van Son & Pols, 1999;Mooshammer & Geng, 2008), and related to prosodic strengthening (Cho, 2005;Cole, Kim, Choi, & Hasegawa-Johnson, 2007), mostly interpreted within the hypoarticulation and hyper-articulation (H&H) theory framework (Lindblom, 1990). In a previous study (Baqué, 2015;Marczyk & Baqué, 2015) involving the same patients, we observed that some segmental phonological contrasts in vowel and consonant productions were enhanced under stress and reduced in unstressed syllables and interpreted these results as possibly related to an H&H phenomena. Thus, further, more focused analyses are needed in order to identify the main factors underlying intensity and duration co-variation in stress contrast marking in conduction aphasics' speech and to determine the extent to which the observed acoustic differences result from a subtle phonetic impairment or are related to speech style and/or monitoring effects (e.g.…”
Section: Discussionmentioning
confidence: 85%
“…Actually such a 'uniform' co-variation between two cues has also been associated in studies about the phonetic realisation of segmental phonological oppositions with 'clear speech' (concomitant strengthening) (Uchanski, 2005;Ferguson & Kewley-Port, 2007) and reduction processes (concomitant weakening) phenomena (van Son & Pols, 1999;Mooshammer & Geng, 2008), and related to prosodic strengthening (Cho, 2005;Cole, Kim, Choi, & Hasegawa-Johnson, 2007), mostly interpreted within the hypoarticulation and hyper-articulation (H&H) theory framework (Lindblom, 1990). In a previous study (Baqué, 2015;Marczyk & Baqué, 2015) involving the same patients, we observed that some segmental phonological contrasts in vowel and consonant productions were enhanced under stress and reduced in unstressed syllables and interpreted these results as possibly related to an H&H phenomena. Thus, further, more focused analyses are needed in order to identify the main factors underlying intensity and duration co-variation in stress contrast marking in conduction aphasics' speech and to determine the extent to which the observed acoustic differences result from a subtle phonetic impairment or are related to speech style and/or monitoring effects (e.g.…”
Section: Discussionmentioning
confidence: 85%
“…Finally, as for error distribution, most authors agree that Broca's aphasics tend to make a greater number of errors in syllable onsets, especially in absolute initial position, due to their difficulty in initiating speech (Marczyk, 2015;Tuller, 1984), and their inadequate articulatory tension (Marczyk and Baqué, 2015). According to the latter authors, the most common errors in initial position are segmental substitutions, which are present in more than 50% of the reported cases, followed by elisions, distortions, contextual substitutions, and additions.…”
Section: Voiceless Stops In Broca's Aphasiamentioning
confidence: 99%
“…However, the literature on such an influence is both extensive and diverse which is why it has not been considered a highly relevant factor in the research -see Machuca (1997) for a more rigorous review on the subject. Second, previous studies have shown that speakers with aphasia tend to produce more errors in syllable onsets and when trying to initiate speech (Marczyk, 2015;Marczyk and Baqué, 2015;Tuller, 1984). Although the reviewed literature does not point at errors related to temporal parameters, it would be interesting to make the distinction between stops in word initial and word medial position when analysing duration values, as well as sonorisation and fricativisation errors.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Ainsi, un locuteur atteint d'une aphasie de type non-fluent avec un déficit de la programmation motrice peut également être atteint d'un déficit phonologique associé. En raison de cela, de nombreuses études avancent l'idée qu'il existe un continuum entre les processus phonologiques et phonétiques dans la production des énoncés (Buckingham et Buckingham, 2015;Marczyck et Baqué, 2015;Laganaro, 2014Laganaro, , 2015. En somme, il existerait, dans l'aphasie, deux origines distinctes possibles pour un trouble, mais une continuité constante entre encodage phonologique et encodage phonétique (Buckingham et Christman, 2008).…”
unclassified
“…Elles font pour cela l'objet de recherches approfondies. La majorité des travaux qui s'y consacre se concentre sur les erreurs d'origine phonétique et principalement sur le phonème, ainsi que sur les traits distinctifs 2 et leurs réalisations (Marczyk et Baqué, 2015;Verhaegen et al, 2020Verhaegen et al, , 2018Verhaegen et al, , 2016. Il est admis que certains phonèmes ou certains traits distinctifs posent des difficultés indéniables aux locuteurs.…”
unclassified